Gaping and loss of fillet firmness in farmed salmon (Salmo salar L.) closely correlated with post‐slaughter cleaning of the abdominal cavity. (2nd September 2015) - Jacobsen, Ása; Joensen, Hóraldur; Eysturskarð, Jonhard
Abstract: This study analysed the effect of cleaning intensity of the abdominal cavity and storage temperature from slaughter to the end of processing on the quality of farmed salmon ( Salmo salar L.) fillets. These two parameters were manipulated in an experimental setup using in total thirty salmon with an average weight of 4.2 kg. The experiment was designed to imitate realistic scenarios in a normal production process in the Faroe Islands. The salmon stored at low temperatures had an average muscle temperature of 4.65°C, whereas the salmon stored at ambient temperature had an average muscle temperature of 11.27°C. After the salmon were gutted to remove all viscera except the kidney, the abdominal cavity was either rinsed lightly or meticulously cleansed of kidneys, all blood and bodily fluids. A wide range of quality and production parameters were measured either straight after cleaning or after the salmon had been stored in chipped ice at 1.5°C for 7 days. All measured parameters were analysed for possible correlations by principal component analysis (PCA). Blood and remains left in the abdominal cavity were shown to have a significant negative effect on fillet firmness ( P < 0.01) and gaping ( P < 0.01). The different storage temperatures between slaughter and gutting, tested in this experiment, did not significantly affect fillet firmness or gaping. However, the fillet colour showed significant negative correlation ( P < 0.01) with the storage temperatures applied.